2021
DOI: 10.3389/fmed.2020.622877
|View full text |Cite
|
Sign up to set email alerts
|

Strongest Correlation Between Contrast Sensitivity and Morphological Characteristics in Bilateral nAMD

Abstract: In patients with neovascular age-related macular degeneration (nAMD) there is often an inconsistency between their subjective visual impairment and a still relatively preserved standard Early Treatment of Diabetic Retinopathy Study (ETDRS) best corrected visual acuity. Therefore, in order to better capture the specific functional defects in nAMD, other tests need to be evaluated. In a previous study, we reported contrast sensitivity of the better eye to best correlate with near distance and distance vision rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Campbell and Robson ( 36 ) suggested that contrast sensitivity in low spatial frequencies may be related to the function of Y-cell channels in peripheral retina, and contrast sensitivity in high spatial frequencies may be related to the function of X-cell channels in central vision. Under well controlled conditions, CSF has been used to evaluate retinal function in many studies ( 12 16 ). For example, Hoffmann et al ( 12 ) measured visual functions and morphologic parameters of the retina in patients with age-related macular degeneration (AMD) and found that among all the measures of visual function, the CSF correlated best with anatomic features of the retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Campbell and Robson ( 36 ) suggested that contrast sensitivity in low spatial frequencies may be related to the function of Y-cell channels in peripheral retina, and contrast sensitivity in high spatial frequencies may be related to the function of X-cell channels in central vision. Under well controlled conditions, CSF has been used to evaluate retinal function in many studies ( 12 16 ). For example, Hoffmann et al ( 12 ) measured visual functions and morphologic parameters of the retina in patients with age-related macular degeneration (AMD) and found that among all the measures of visual function, the CSF correlated best with anatomic features of the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Under well controlled conditions, CSF has been used to evaluate retinal function in many studies ( 12 16 ). For example, Hoffmann et al ( 12 ) measured visual functions and morphologic parameters of the retina in patients with age-related macular degeneration (AMD) and found that among all the measures of visual function, the CSF correlated best with anatomic features of the retina. As previous studies have shown, damages in the retinal and choroidal vascular support, such as vascular bed disease, can lead to severe visual impairment ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al ( 36 ) also found the correlation between decreased macular sensitivity and morphologic degeneration of photoreceptors in high myopes using microperimetry and adaptive optics. Hoffmann et al ( 37 ) measured visual function and retinal morphologic parameters in patients with age-related macular degeneration and found correlations between contrast sensitivity and retinal anatomic features. They suggested that CSF may serve as a better biomarker in early disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OCTA is non-invasive, which means it is safer in clinics. There have been other studies on diseases, such as diabetes ( 31 ) and age-related macular degeneration ( 32 ), found that the reduced contrast sensitivity was associated with VD. So we chose OCTA to explore the correlation between retinal structure and contrast sensitivity.…”
Section: Introductionmentioning
confidence: 98%